Randomized clinical trials regarding frenectomy with conventional surgical method and laser techniques in children and adolescents. Literature Review - Alarcón-Calle, Catherine Sharlot (2024)
Objective: To report on randomized clinical studies that compare clinical performance of conventional surgical method and laser technique in frenectomies in children and adolescents. Material and Methods: A bibliographic search was carried out in the Scopus, PubMed/Medline and Web of Science databases. Articles in English, Spanish and Portuguese published in the last 15 years were included, whose content was related to frenectomies performed with laser or conventional surgery in children and adolescents. To describe clinical performance, variables such as pain, surgery time, bleeding, use of analgesics, healing, and swallowing or speaking problems were considered. Randomized controlled, blinded, double-blind or non-randomized clinical studies were included. After an evaluation according to inclusion criteria based on titles and full text of each article, 7 articles were included. Conclusion: Frenectomy performed with laser technique have demonstrated better clinical performance in terms of less pain, less surgery time, less analgesic medication, and fewer postoperative complications such as swallowing, and speech problems compared to conventional surgery with the use of a scalpel.